Leptin induces TNFα-dependent inflammation in acquired generalized lipodystrophy and combined Crohn’s disease - Jörn F. Ziegler (Nature Portfolio, 2019)
The adipokine leptin modulates intestinal inflammation in mice. Here the authors describe a patient with inflammatory bowel disease and lipodystrophy, providing evidence that leptin aggravates intestinal inflammation with proinflammatory effects on leukocytes that are reversible by TNFα blockade.